2019
DOI: 10.5853/jos.2019.01277
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the ELAPSS Score for Prediction of Unruptured Intracranial Aneurysm Growth Risk

Abstract: Background and Purpose Prediction of intracranial aneurysm growth risk can assist physicians in planning of follow-up imaging of conservatively managed unruptured intracranial aneurysms. We therefore aimed to externally validate the ELAPSS (Earlier subarachnoid hemorrhage, aneurysm Location, Age, Population, aneurysm Size and Shape) score for prediction of the risk of unruptured intracranial aneurysm growth. Methods From 11 international cohorts of patients ≥18 years with ≥1 unruptured intracranial aneurysm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Although two studies showed that ELAPSS score was associated with IA growth (18,20), the c-statistic was 0.72 in the development cohort at 3 and 5 years (20). Meanwhile, in a retrospective study of ruptured IAs, 45.5% of patients were classified as low or intermediate risk using the ELAPSS score (31).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although two studies showed that ELAPSS score was associated with IA growth (18,20), the c-statistic was 0.72 in the development cohort at 3 and 5 years (20). Meanwhile, in a retrospective study of ruptured IAs, 45.5% of patients were classified as low or intermediate risk using the ELAPSS score (31).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, determining the risk factors for UIA progression would be of substantial clinical value. Many previous studies have investigated the risk factors for IA progression (2,4,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the results are not consistent.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent literature has suggested that several groups of aneurysms have a higher risk of growth than others, and these patients may benefit from shorter intervals of repeated surveillance imaging. 129,130 The ELAPSS score has been used to predict the risk of aneurysmal growth, such that earlier SAH, location of aneurysm, age >60 years, population, and size and shape of the UIA were found to be predictors of aneurysmal growth. 129 This score was externally validated and was found to show accurate calibration for 3-and 5-year risks of aneurysm growth.…”
Section: Managementmentioning
confidence: 99%
“…As a result, this score may assist patients and clinicians in predicting the growth of a UIA and in planning for followup imaging accordingly. 130 Furthermore, in elderly patients (>75 years) and those with significant comorbidities or a limited life expectancy, conservative management and no follow-up may be needed, even with large aneurysms, because it is highly unlikely that these patients will undergo preventive aneurysm treatment.…”
Section: Managementmentioning
confidence: 99%